Congenital plasmodium vivax malaria mimicking neonatal sepsis: a case report - Dr Anil Jain; Dr. Devina Saraswat (Pediatric Review: International Journal of Pediatric Research, 2015)
A case of congenital malaria by plasmodium vivax initially mistaken for neonatal sepsis is described. Correct diagnosis requires high index of suspicion with inclusion of congenital malaria in the differential diagnosis of neonatal sepsis even if the mother has no proven malaria episodes during gestational period.